Application of Guided Imagery Therapy in Hypertension Patients at Kartini General Hospital Karanganyar - Rahmawanti, Dinda; Mulyaningsih; Listyorini, Dewi (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Background: Guided imagery therapy is a technique that uses an individual's imagination with the specific aim of achieving control and relaxation. Relaxation can have a direct effect on bodily functions. The effects of relaxation include reducing muscle tension, improving concentration, lowering respiratory rate and pulse, as well as decreasing blood pressure. Objective: To determine the effectiveness of Guided Imagery therapy in reducing blood pressure among hypertensive patients at Kartini General Hospital Karanganyar. Methods: This study employed a descriptive case study approach, involving two hypertensive patients at Kartini General Hospital Karanganyar who had high blood pressure. The therapy was administered once daily for 20 minutes over a period of one day. Results: After undergoing Guided Imagery therapy for one day (one session of 20 minutes conducted in the afternoon), both respondents showed a reduction in blood pressure. Conclusion: Guided Imagery therapy has proven effective in helping to lower blood pressure among hypertensive patients and can be recommended as a management strategy for reducing blood pressure in hospital settings and the broader community.